Evaluation of PCB materials for high frequency power applications using MOORA method. Issue 1 (1st February 2022) - Ratna, Sanatan; Narayan Vishwakarma, Prem; Ojha, Manish; Kannojiya, Ravindra; Shubham, Pritish; Sharma, Shubham
Abstract: One of the first and foremost steps in design is the material selection. The selection of the best available material is quite important for the product as it influence the final quality and performance of the product. The materials used generally for printed circuit board (PCB) similarly requires shortlisting based on several factors which affect the durability and the functionality of the PCB assembly. Selecting the correct PCB material requires a knowledge of the available materials and their physical characteristics and how they align with the required functionality of the board. In the current research work, four factors namely, thermal conductivity, dissipation factor, moisture absorption and dielectric constant are used to evaluate nine PCB materials under consideration for high frequency applications. The evaluation of the nine PCB materials under consideration based on the four factors listed above is done using MOORA method (Multi-objective optimization on the basis of ratio analysis). The analytical tool used here makes a comprehensive list of PCB materials while considering the multi-conflicting material selection attributes. The assessment value of the alternatives with respect to all the criteria is calculated and compared for all the nine materials chosen. The final ranking is done, based on the assessment values of the nine alternatives for high frequency applications. The alternative with the highest assessment value is ranked one and is the most obvious choice while the one with the least assessment value is the least preferred material and is to be avoided.